SISTEM KOMPUTERISASI PENGOLAHAN DATA TUGAS AKHIR MAHASISWA USAHID - Heri Kusharyanto; Dwi Retnoningsih; Dahlan Susilo (JURNAL GAUNG INFORMATIKA, 2013)
The final project data processing in Sahid Surakarta University still uses manual data processing system today. Data recording of final project to the final exam sub mission, does not uses particular application for final project data processing. This way, however has some weakness specially it is often occurred, some errors and takes a long time in recording and searching the data. The objective of this research to construct a system of data system is the processing of data and information which operated manually converted to application program. The converting is required to make the data processing and information access easily. It is due to the fact that many weakness which is encountered in manually data processing system can be avoided.